Leveraging Robotic Process Automation for Enhancing Operational Efficiency and Agility in Warehouse Management Systems - Iyengar, Sampath Ramesh; Sivakumar, V.; Ruthramathi, R. (Indian Journal of Information Sources and Services, 2026)
Warehouse Management Systems (WMS) are increasingly being demanded to process high order volumes, handle demand variability, and manage operational complexity, which can be challenging in manual and semi-automated warehouse operations. Such restrictions lead to delays, errors, and reduced responsiveness, especially during peak operations. To resolve these issues, this paper analyses the implementation of Robotic Process Automation (RPA) as a non-invasive automation layer on an existing warehouse management system. The solution suggested aims to automate routine, rule-based warehouse operations, including order processing, inventory updates, and transaction recording, without any changes to the fundamental WMS. The implementation and evaluation of an RPA-based operational structure are based on real warehouse transaction data collected over a long period of operational activity. Performance is measured in terms of agility, operational efficiency, and the accuracy of system behavior before and after automation. The results show that integrating RPA can accelerate task execution, minimize human involvement, and enhance process consistency. Moreover, the system is more flexible in responding to changes in workload and becomes more coordinated in warehouse operations. The paper summarizes that RPA can be a viable, scalable solution for improving warehouse operations, especially when the organization wants to automate processes on a smaller scale without massive system restructuring. The work offers valuable information to practitioners and researchers who may wish to implement software-based automation in the current warehouse management setting.